Uji Aktivitas Antioksidan Ekstrak Etil Asetat Daun Tigaron (Crateva Religiosa) Menggunakan Metode DPPH - Rosya Rizky Maulidya; Revita Saputri; Liana Fitriani Hasymi (BORNEO JOURNAL OF PHARMASCIENTECH, 2023)
Tigaron leaf methanol extract (Crateva religiosa) was reported to have activity as a very strong antioxidant. Differences in solvents in extracts can affect the results of pharmacological activity, for example, ethyl acetate solvent on antioxidant activity, so the purpose of this study was to determine the results of phytochemical screening and antioxidant activity of the ethyl acetate extract of Tigaron leaves (Crateva religiosa). Phytochemical screening was carried out qualitatively, while antioxidant activity was carried out quantitatively using the DPPH (2,2-Diphenyl-1-picrylhydrazyl) method using a UV-Vis spectrophotometer and quercetin comparator. The ethyl acetate extract of Tigaron leaves (Crateva religiosa) was extracted by maceration method. Phytochemical screening tests obtained positive results for the alkaloids, flavonoids, and steroids. Antioxidant testing using the comparator quercetin obtained IC50 results of 3.4384 ppm and the ethyl acetate extract of Tigaron (Crateva religiosa) leaves obtained IC50 results of 114.0457 ppm. It can be concluded that the ethyl acetate extract of Tigaron leaves (Crateva religiosa) has moderate potential as an antioxidant.